2006
DOI: 10.1002/hfm.20047
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-based assessment of product creativity: A review and reappraisal

Abstract: In the current value-based economy, organizations compete to match customer needs and requirements by adding various types of value to products or programs. One example of this added value is product creativity, which is defined as the originality and appropriateness of a product that elicits a positive affect compatible with the consumer or judge. In this article, the authors review current research on creativity, product development, and consumer behavior and reappraise the current tools to measure product c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 36 publications
2
79
0
1
Order By: Relevance
“…The result matches the concepts of Jan & Christian (2005), Horn & Salvendy et al (2006). It means that when tourists are identified with innovation marketing, which can directly respond to diverse needs, it can enhance tourists' experiential value.…”
Section: Conclusion and Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The result matches the concepts of Jan & Christian (2005), Horn & Salvendy et al (2006). It means that when tourists are identified with innovation marketing, which can directly respond to diverse needs, it can enhance tourists' experiential value.…”
Section: Conclusion and Discussionsupporting
confidence: 78%
“…Rogers (1995) suggested that product innovation can enhance consumers' positive value. Horn & Salvendy (2006) indicated that if we provide more information of innovative products to consumers, we will positively enhance consumers' experiential value. Based on the above, innovation positively influences customer value.…”
Section: Relationship Between Innovation Marketing and Experiential Vmentioning
confidence: 99%
“…This also applies to those who assert the product-or press-based views of creativity. Accordingly, the instruments used by these researchers often have a particular focus and reflect only a narrow range of the aspects of the creativity construct (Baer & McKool, 2009;Horn & Salvendy, 2006; Lemons, Said-Metwaly, S., Kyndt, E., den Noortgate, W. V. Methodological Issues in Measuring Creativity: ...…”
Section: Selecting Measurement Instrumentsmentioning
confidence: 99%
“…According to (Besemer & O'Quin, 1999) original ideas are unusual or infrequently seen in a universe of products, while the surprise component is related to reactions to unexpected or unanticipated information. Additional characterizations are added in later publications, consisting in style (Horn & Salvendy, 2006), i.e. the degree to which a product combines unlike elements into a coherent whole, and germinability, i.e.…”
Section: Surprise As a Characteristic Of Novel Productsmentioning
confidence: 99%